Mortality from cardiovascular diseases and exposure to inorganic mercury. Issue 7 (1st July 2001) - Boffetta, P; Sällsten, G; Garcia-Gómez, M; Pompe-Kirn, V; Zaridze, D; Bulbulyan, M; Caballero, J-D; Ceccarelli, F; Kobal, A B; Merler, E
Abstract : OBJECTIVE: To study the mortality from cardiovascular and other chronic non-neoplastic diseases after long term exposure to inorganic mercury. Limited information is available on the effect of chronic exposure to mercury on the cardiovascular system. METHODS: The mortality was studied among 6784 male and 265 female workers from four mercury mines and mills in Spain, Slovenia, Italy, and the Ukraine. Workers were employed between 1900 and 1990; the follow up period lasted from the 1950s to the 1990s. The mortality of the workers was compared with national reference rates. RESULTS: Among men, there was a slight increase in overall mortality (standardised mortality ratio (SMR) 1.08, 95% confidence interval (95% CI) 1.04 to 1.12). An increased mortality was found from hypertension (SMR 1.46, 95% CI 1.08 to 1.93), heart diseases other than ischaemic (SMR 1.36, 95% CI 1.20 to 1.53), pneumoconiosis (SMR 27.1, 95% CI 23.1 to 31.6), and nephritis and nephrosis (SMR 1.55, 95% CI 1.13 to 2.06). The increase in mortality from cardiovascular diseases was not consistent among countries. Mortality from hypertension and other heart diseases increased with estimated cumulative exposure to mercury; mortality from ischaemic heart disease and cerebrovascular diseases increased with duration of employment, but not with estimated exposure to mercury. Results among women were hampered by few deaths. CONCLUSION: Despite limited quantitative data on exposure, possible confounding, and likely misclassification of disease, the study suggests a possible association between employment in mercury mining and refining and risk in some groups of cardiovascular diseases.